Chemical ozone loss in a chemistry-climate model from 1960-1999 - Lemmen, Carsten; Dameris, Martin; Müller, Rolf; Riese, Martin (Geophysical Research Letters, 2006)
In the recent WMO assessment of ozone depletion, the minimum ozone column is used to assess the evolution of the polar ozone layer simulated in several chemistry-climate models (CCMs). The ozone column may be strongly influenced by changes in transport and is therefore not well-suited to identify changes in chemistry. The quantification of chemical ozone depletion can be achieved with tracer-tracer correlations (TRAC). For forty Antarctic winters (1960–1999), we present the seasonal chemical depletion simulated with the ECHAM4.L39(DLR)/CHEM model. Analyzing methane–ozone correlations, we find a mean chemical ozone loss of 80 ± 10 DU during the 1990s, with a maximum of 94 DU. Compared to ozone loss deduced from HALOE measurements the model underestimates chemical loss by 37%. The average multidecadal trend in loss from 1960 to 1999 is 17 ± 3 DU per decade. The largest contribution to this trend comes from the 62 ± 11 DU ozone loss increase between the 1970s and 1990s.